Simulation Database System of the Active Ingredients in Compound Decoction of Chinese Medicine - Zhang , Long; Zhao , Hua; Zhou , Gang; Niu , Tianshui; Yang , Jianshe (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
Compound decoction is the main form of clinical application of Chinese medicine. Current research on active ingredients of Chinese medicine has commonly relied on chemical separation and extraction technology by using organic solvents, which was very different from the traditional method of water-phase boiling. Difference in preparation methods would lead to awareness discrepancy in active ingredients. The present system simulated the decoction boiling conditions of traditional Chinese medicine, and established databases of related components and their interaction, and analysed the possible active ingredients existed in compound decoction via database mining, statistical analysis and other technologies.